Development of patient-tailored preoperative assessment of percutaneous vertebroplasty - Lu, Yian; Jiang, Qunhua (Frontiers in Surgery, 2024)
Percutaneous vertebroplasty (PVP), a minimally invasive surgery technique, has become the common treatment for osteoporotic vertebral compression fractures (OVCF). The complications of PVP will lead to severe damage to spinal neuro systems due to bone cement leakage. A patient tailored preoperative assessment approach was developed to reduce the risks of complications in this study. The porcine OVCF model was fabricated to mimic the patient vertebral fracture in vitro using decalcification process. The 3D reconstructed model based on the imagological examination data acquired from the porcine vertebral bone was implemented for finite element (FE) simulation. The vertebral body with bone cement injected was scanned using CT for comparison with the finite element simulation results. This study showed a practical method for predicting the flow of bone cement in OVCF, which enabled the surgeons to evaluate the bone cement flow during preoperative assessment to reduce the cement leakage risks.